PENGARUH CITRA DAN KEPERCAYAAN TERHADAP NILAI PELANGGAN DAN DAMPAKNYA PADA KEPUASAN SERTA LOYALITAS NASABAH - ., Solechah; Soliha, Euis (Proceeding Fakultas Ekonomi, 2015)
This study aimed to analyze the effect of the image and trust on customer satisfaction and their impact to customer satisfaction. Samples are 98 respondents, the sampling technique used purposive sampling is sampling based on the criteria set forth, among others: (1) Respondent that the research sample are customers who use the services of storage savings for at least 1 year, (2 ) Customers are already transacting 1 times. Analysis of data is used multiple regression analysis. Test results show that (1) there is significant positively affects the image on the customer value, (2) there is significant positively affects trust on the customer value, (3) there is significant positively affects the image on the customer satisfaction, ( 4) there is significant positively affects trust on customer satisfaction, (5) there is significant positively affects customer value on customer satisfaction. Keywords: image, trust, customer value, and satisfaction